Simulasi Surge Tsunami Dengan Metode Dam Break Menggunakan Reservoar Terbatas - Bangguna, David; M. Tangkeallo, Marthen; O. Pandoyu, Ebelhart; Pujiono, Pujiono; E. Wuon, Orva; B. Pakpahan, Irnovia (Jurnal Teknik Sipil, 2024)
Abstract The dam break method for simulating tsunami surges in the laboratory typically uses a sufficiently long flume, so that the upstream section of the flume, which serves as the reservoir, is also quite long. Using a long reservoir can provide a more extended simulation time for tsunami surge propagation on land, allowing the characteristics of the tsunami surge to be well observed. With a shorter flume, the reservoir space is also limited in length, and the simulation time for tsunami surge propagation is likewise constrained. This study aims to describe the characteristics of the simulated tsunami surge in comparison to the Chanson solution using a limited (short) reservoir. The tsunami surge simulation in a dry channel was conducted under the assumption of a limited reservoir with no bed slope. The water height in the reservoir varied from (d0) = 100 mm, 200 mm, 300 mm, and 400 mm, and the simulation was performed three times for each reservoir height. The tsunami surge simulation with downstream inundation was conducted similarly, but with an initial downstream inundation height of d1 = 100 mm and 150 mm, without initial velocity. The analysis results showed that the height and velocity of the tsunami surge from the simulation for both dry and inundated channels approached the results from Chanson's solution. This indicates that a limited flume length can be used to simulate tsunami surges with the dam break method, and that simulations with initial inundation can simulate the waveforms of undular bore and fully developed bore.